A Concise Cross-Metathesis Route to Enantiopure 1-Azaspirocycles - Wang, Zhen James; Spiccia, Nicolas Daniel; Gartshore, Christopher James; Illesinghe, Jayamini; Jackson, William Roy; Robinson, Andrea Jane (Synthesis, 2013)
A concise synthesis of spiropyrrolidines and spiropiperidines has been developed. The approach employs a ruthenium–alkylidene-catalysed cross-metathesis reaction of enantiopure N-protected allylglycine with methylenecycloalkanes. The resultant alkene intermediates can then undergo a tandem acid-catalysed cyclisation to form spiropyrrolidines. Ring expansion of the spiropyrrolidine system, via an aziridinium intermediate, grants access to the homologous spiropiperidine ring system with excellent stereoretention.
Keywords: spiro compounds; metathesis; ring expansion; catalysis; piperidines; pyrrolidines